2001
DOI: 10.4049/jimmunol.166.10.6134
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of CD28 Expression by CD28GR, a Novel Promoter Element Located in Exon 1 of the CD28 Gene

Abstract: CD28 provides an essential costimulatory signal required for Ag-mediated T cell activation via the TCR. Although accumulating evidence exists for the signaling properties of CD28, less is known regarding the regulation of CD28 expression. In this study, we have identified a novel promoter element of CD28, CD28GR (GGGGAGGAGGGG), which is located between +181 and +192 in exon 1 of the CD28 gene. Mutations within the 12-bp CD28GR sequence abolished its transcriptional activity. CD28GR contains a Sp1/EGR-1 binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…It contained additional 5Ј sequences flanking the minimal CD28 promoter sequences in the p42 and p52 reporters (3). We had reported previously that the activity of the CD28 minimal promoter was regulated by the CD28 INR (33), which functioned independently of a downstream GR element (41). To further validate that the CD28 INR comprised the minimal promoter, the GR element was deleted in the RV construct, the shortest of the reporters.…”
Section: Methodsmentioning
confidence: 99%
“…It contained additional 5Ј sequences flanking the minimal CD28 promoter sequences in the p42 and p52 reporters (3). We had reported previously that the activity of the CD28 minimal promoter was regulated by the CD28 INR (33), which functioned independently of a downstream GR element (41). To further validate that the CD28 INR comprised the minimal promoter, the GR element was deleted in the RV construct, the shortest of the reporters.…”
Section: Methodsmentioning
confidence: 99%
“…Our data indicate that enforced expression of Egr1, 2, and 3 increases the surface expression of CD28. It was recently demonstrated that Egr1 can transactivate reporter constructs containing G-rich CD28, a novel promoter element within CD28 exon 1 which serves as the predominant cis-acting element for regulating CD28 expression (46). Consequently, induction of the Egr factors during traversal of the ␤-selection checkpoint is likely to play an important role in the transactivation of CD28 during development of DN thymocytes to the DP stage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that CD28 transcription may also be regulated by Sp1 and Egr-1 proteins, which bind to a so-called GR element situated in the first exon of the gene (49). The GR sequence is likely an enhancer element as evidenced by observations that the pharmacologic agent phytohemagglutinin increases the activity of GR-driven reporter gene constructs.…”
Section: Fig 11 Nucleolin⅐hnrnp-d0a⅐site ␣-Complex Formation Is Permentioning
confidence: 99%
“…The GR sequence is likely an enhancer element as evidenced by observations that the pharmacologic agent phytohemagglutinin increases the activity of GR-driven reporter gene constructs. It may be noted that the GR element is 30-bp upstream from the first translation codon (49), whereas the ␣␤-INR is situated 130-bp further upstream in the 5Ј-untranslated region (10) and coincides with the transcription initiation site (50). Unlike the enhancer activity of the GR sequence, the ␣␤-INR is a core promoter element regulating the constitutive transcription of CD28 (18).…”
Section: Fig 11 Nucleolin⅐hnrnp-d0a⅐site ␣-Complex Formation Is Permentioning
confidence: 99%